Awareness, knowledge and attitude towards informed consent among doctors in two different cultures in Asia: a cross-sectional comparative study in Malaysia and Kashmir, India - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi; How, Soon Hin; Rasool , A G; Rehana , K (Singapore Medical Association, 2007)
Introduction: Informed consent is now accepted as the cornerstone of medical practice, with reasonable patient standards typically considered to be appropriate in the developed countries; however it is still challenged in many developing countries. The objective of this descriptive study was to evaluate the perceptions and practices among attending medical professionals in matters relating to informed consent in selected hospitals. Methods: A questionnaire-based cross sec tional survey among doctors in the two tertiary care hospitals, one in Malaysia and the other in Kashmir, was performed. Results: Awareness on informed consent was universal with “reasonable physician standard” as the most popular choice. As compared to doctors in Malaysia, doctors from Kashmir showed a tendency to reservedly disclose medical information (p-value equals 0.051) and withhold it, if it was deemed potentially harmful (p-value is less than 0.001) or requested so by relatives (p-value is less than 0.023). They also withheld some information from female patients (p-value is less than 0.001). When consent was refused despite needing lifesaving intervention, the majority of both respondents (73 percent versus 80 percent) considered intervention without consent to be justifi ed. Respondents from Malaysia felt that parents could refuse treatment on their children’s behalf on the basis of their beliefs (p-value is less than 0.001). Conclusion: Despite a very high awareness of informed consent, the model chosen refl ected age-old medical paternalism. Doctors’ opinions are accorded a larger role in clinical decision-making in Kashmir. The results emphasise the need for doctors to change their attitude and acknowledge the patient’s autonomy, which is the basis of modern medical ethics, and yet still be aware of the cultural and religious views of the local population. Keywords: clinical decision-making, informed consent, medical ethics, patient autonomy Singapore Med J 2007; 48(6):559–565 INTRODUCTION